Emotional intelligence in tourism and hospitality / Erdogan Koc - Koc, Erdogan
The contributors to this book explain the influence of emotional intelligence on various aspects of service encounters in tourism and hospitality and how emotional intelligence as an important ability of employees in tourism and hospitality can be developed. The book has 10 chapters with plenty of student support materials including real-life examples, case studies, links to websites, activities and discussion questions, recent research findings from top-tier journals and presentation slides for in-class use by academics and trainers.